Implementation of RADEC Model for Improving Higher Order Thinking Skill (HOTS) in Science Learning at Elementary Schools - Rohmatillah, Nur; Maspiroh, Iyoh; Pujiastuti, Pratiwi (Scientica Education Journal, 2024)
Science learning in elementary schools requires Higher Order Thinking Skills (HOTS), so supportive learning model is needed. This research aims to: 1) describe the application of HOTS in science education at elementary level; 2) describe the RADEC learning model for science learning, and 3) describe the factors that support and hinder the application of RADEC to improve HOTS in science education in elementary schools. This research uses a systematic literature review method or literature review, which focuses on the process of reviewing and analyzing widely and carefully several literature relevant to the research topic. The results of this study show: 1) HOTS is indispensable in science learning; 2) The introduction of RADEC greatly improves the science HOTS skills of elementary students; 3) The application of RADEC to improve students' HOTS is influenced by many factors, including teachers' understanding and competence of the RADEC model, facilities and infrastructure, and teacher support.